Byzantium and the Pechenegs : the historiography of the problem - Mel‘nyk, Mykola Mykolajovyč, 1976- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2022)
This book traces 150 years' worth of scholarly interpretations of relations between Byzantium and various North Pontic nomads, with particular attention to how colonialist or national aspirations often triggered, hampered, biased, or otherwise influenced these interpretations. Original in its interdisciplinary approach, Mykola Melnyk's book highlights an overlooked topic: the history of non-historic peoples. Going beyond the well-studied written sources for nomadic history, the author incorporates insights provided by archaeology, linguistics, and the natural sciences, bringing forth promising avenues of research into the subject of nomadic cultures in the medieval world.